Sistemas de gestión en salud ocupacional en Córdoba. Caso de los hospitales (2016)
The aim of the present article is to evaluate Occupational Health management systems in medium-level Public health-care institutions of Cordoba (Colombia). The research method used a quantitative approach of a descriptive type with a cross-sectional design with non probability sampling through surveys conducted to four Occupational health coordinators and checklists based on approved technical standards (Occupational Health and Safety Assessment Series, version 18001). Data was processed with Statistical Package for the Social Sciences (version 20) with multivariate analysis. Results showed that all four institutions in Cordoba have 1,550 employees; 100% do not have a budget assigned to the field of safety and occupational health management system; 75% lack information; 75% do not perform research or monitoring of occupational accidents, 75% of coordinators lack specific training regarding their own positions; and 45% are concerned about structuring and maintaining healthy habits. Finally, the discussion phase shows that there are management weaknesses in the systems since, for instance, system elements are identified but they are not linked, they just work as support material for exclusive documents.